Pengaruh Brand Awareness, Promosi dan Citra Merek terhadap Keputusan Pembelian Produk Pie Susu Ajik Krisna Oleh-Oleh Bali - Sisilia Ananda Santoso; Kadek Wulandari Laksmi P (ManBiz: Journal of Management and Business, 2025)
The purpose of this study was to determine the effect of brand awareness, promotion, and brand image on purchasing decisions for Ajik Krisna milk pie products, Balinese souvenirs. This study was conducted in Denpasar City and Badung Regency, Bali, as the operational centers of PT. Krisna Nusantara Group and the main locations for Ajik Milk Pie consumers. The population in this study was all consumers of Ajik Milk Pie whose number was not known for certain. Therefore, the sample determination used a non-probability sampling technique with the criteria of having purchased Ajik Milk Pie at least once in the last six months and being at least 17 years old. The sample size was determined based on Rambut guidelines, namely the number of indicators multiplied by a scale of 10 to obtain 180 respondents. Based on the results of the research that has been conducted, it can be concluded that the three variables studied, namely, brand awareness, promotion, and brand image have a positive influence on consumer purchasing decisions for Ajik Krisna Milk Pie. This finding indicates that the higher the level of consumer awareness of the brand, the more effective the promotional strategy carried out, and the better the company's brand image, the greater the consumer's tendency to make a purchase. Thus, efforts to improve these three aspects simultaneously will make a direct contribution to improving consumer purchasing decisions.